PRESENT DAY TECTONIC GRADIENT IN NINH THUAN AND SURROUNDING REGION - Trinh, Phan Trong; Liem, Ngo Van; Hai, Vy Quoc; Phong, Tran Van; Huong, Nguyen Van; Thuan, Nguyen Viet; Xuyen, Nguyen Quang; Thom, Bui Van; Tuc, Nguyen Dang; Vinh, Hoang Quang; et al. (Vietnam Journal of Marine Science and Technology, 2015)
The estimation of the present day tectonic movement and tectonic gradient (strain rate) has an important practical signification in the assessment of active fault and seismic hazards for the selection of Ninh Thuan nuclear power plant. Based on the three campaigns of GPS measurement between 2012 - 2013, we used BERNESE 5.0 software to determine present day slip rates of 13 stations in ITRF08 frame. The GPS stations move eastwards at the slip rates of 22 - 25 mm/yr, southwards at the velocities of 5 - 10 mm/yr. The standard errors in latitudinal and longitudinal directions are 1.2 mm/yr and 0.9 mm/yr, respectively. Combined with GPS data from the project of the study on actual geodynamics in Tay Nguyen TN3/06, we determined the strain rate ranging from 50 to 100 nanostrains with the standard error of 50 nanostrains. The direction of maximum compressive strain rate is from northwest - southeast to east - west.